Case report: A rare case of coexistence of low-grade appendiceal mucinous neoplasia and goblet cell adenocarcinoma in the appendix - Zhou, Ping; Yu, Xuejiao; He, Du (Frontiers in Oncology, 2024)
Background Primary appendiceal tumors are rare. Low-grade appendiceal mucinous neoplasia (LAMN) and goblet cell adenocarcinoma (GCA) account for 20% and 14% of primary appendiceal tumors, respectively. The coexistence of LAMN and GCA is an extremely rare event. This report presents a case of an elderly male patient with an appendiceal tumor composed of LAMN and GCA in the same appendix. Case presentation A 72-year-old male patient was admitted to our institution presenting with a history of abdominal pain localized to the right lower quadrant for two months. Abdominal computed tomography (CT) showed a large dilated thickened cystic mass in the appendix, along with a small duodenal diverticulum. Laboratory tests indicated elevated levels of serum carcinoembryonic antigen (CEA) and cancer antigen 199 (CA19-9) markers. The patient underwent a laparoscopic right hemicolectomy and exploration of the duodenal diverticulum, and there was no finding of perforation of the duodenal diverticulum. Focal positivity for chromogranin A (CgA) and synaptophysin (Syn) was observed in the tumor cells of GCA. The final pathological diagnosis revealed the coexistence of LAMN staged pT4a and grade 1 GCA staged pT3 in the appendix. Unfortunately, the patient died due to severe septic shock and circulatory failure secondary to a perforated duodenal diverticulum. Conclusions The coexistence of LAMN and GCA are extremely rare in the appendix and may result from the proliferation of two independent cellular lines. The coexistence of distinct neoplasms poses diagnostic and management challenges. Multidisciplinary team discussion may be essential in the effective management of these patients.